Short Communication: Prevalence of hypertension and variation of blood pressure with age among adolescents in Chetla, India - Saha, I; Paul, B; Dasgupta, A (Tanzania Journal of Health Research, 2008)
This community-based cross-sectional study was carried out to determine the prevalence of hypertension and variation of blood pressure with age among adolescents in an urban slum of Chetla, Kolkata, India. A total of 1081 adolescents aged 10-19 years were involved in the study. The prevalence of hypertension was 2.9% (31) and highest prevalence (5.6%) was observed in the age group of 18-19 years. The mean systolic and diastolic blood pressure was higher in males than females. Among males and females, average increase of mean systolic blood pressure was found to be 2.26mmHg and 1.95mmHg per year respectively. The mean diastolic blood pressure increased by 1.55 mmHg and 1.42mmHg per year, respectively. The age spurt of rise in mean systolic blood pressure in males was found at 10-11, 13-14, and 16-17 years age groups, whereas in females it was observed in 12-13, and 17-18 years age groups. The age spurt of rise in mean diastolic blood pressure in males was observed in the age group 16-17 years and in females it was noted in the age group 11-12, and 17-18 years. In conclusion, blood pressure measurement should be done routinely during health check up ofadolescents to initiate secondary level of prevention at the earliest. Keywords: adolescents, hypertension, India Tanzania Journal of Health Research Vol. 10 (2) 2008: pp. 108-111